Gut microbiota modulation and immunity enhancement by Bacillus amyloliquefaciens NL1.2: A fiber-degrading probiotic isolated from native Thai swine - Kittiya Khongkool; Malai Taweechotipatr; Sunchai Payungporn; Vorthon Sawaswong; Monthon Lertworapreecha (Veterinary World)
Background and Aim: The pursuit of sustainable alternatives to antibiotic growth promoters has intensified interest in spore-forming probiotics with fiber-degrading capabilities. This study aimed to isolate, characterize, and evaluate the safety and functional properties of Bacillus spp. from native Thai swine, focusing on strains with probiotic potential and enzymatic activity for application in livestock nutrition.